Paradoxes of the poetry of the Soviet totalitarian discourse: the religious images and motifs as reprezentants of the ideology - Літвінова, Інна Миколаївна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”)
The article investigates the religious images and motives as the spokesmen of the communist ideology in the poetry of the totalitarian discourse. Rejecting religion in general, Soviet ideology extensively uses the conceptual framework of Christianity, replacing nomination. The proof of this is the paradox of poetic images of the analyzed texts.